FAKTOR BUDAYA, KOMUNIKASI DAN PANDANGAN MASYARAKAT PENYEBAB KETERTINGGALAN MENTAL MASYARAKAT BADUI (STUDI KASUS PADA MASYARAKAT BADUIH NAGARI SIMAWANG KECAMATAN RAMBATAN KABUPATEN TANAH DATAR) - Ermairel Salim (Ensiklopedia of Journal, 2021)
This research was conducted in Jorong Baduih Nagari Simawang, Rambat Subdistrict, Tanah Datar District, entitled Cultural Factors, Communication and Community Views, Causes of Mental Behind the Baduih Society (Case Study on Baduih Nagari Simawang Community, Rambat Subdistrict, Tanah Datar District) This study aims to determine the Cultural, Communication, and Community Views Factors of the Causes of Mental Behind the Baduih Society. The benefits of research are expected to be useful from both theoretical and practical aspects. Theoretically, this research is expected to be useful for the development of communication science, providing information and contributing communication ethics. Practically, this research is expected to be useful as information for individuals and society in cultured and good mental attitude. The time of the implementation of this research starts from March 2018 until June 2018. Data collection techniques are by interview, observation and documentation. Data Analysis Techniques with qualitative data analysis. From the results of the study obtained factors of culture, communication and community views causing mental retardation Baduih community. The mental retardation of the community is very difficult to change, so it is recommended to the Regional Government that needs to be done in community development so that the right target is to build the mentality of people who are left behind.